Microbial Resistance Trends in Pediatric Chronic Rhinosinusitis: Insights from South India - Madhavi Jangala; Raja Meghanadh Koralla; Santoshi Kumari Manche; Pardhanandana Reddy Penuguluru; Jyothy Akka (Research Perspectives of Microbiology and Biotechnology Vol. 7, 2024)
Objective: Chronic rhinosinusitis (CRS) is a common upper respiratory disease with a significant role of microbes in worsening the disease and its associated co-morbidities. In India, studies on the etiology and antibiotic resistance in CRS are limited, especially in children. Antibiotic administration can facilitate the subsequent proliferation of a variety of bacteria, frequently leading to the emergence of novel multidrug-resistant strains on the mucosal epithelium, with such frequencies and alterations potentially varying according to the type of antibiotics employed, age demographics, and clinical presentations. Aim: The present study aimed to determine the prevalence of common causative microbes and their antibiotic resistance in children and adolescents with CRS in the South Indian population. Subjects and Methods: The present study was conducted on 89 children and 99 adolescents with CRS who visited MAA ENT Hospital, Hyderabad, South India. Conventional and VITEK-2 methods were used for the identification and antibiotic sensitivity of the microbes. The diagnostic criteria for nasal allergy were primarily determined through the presence of symptoms including nasal discharge, nasal pruritus, and sneezing occurring more than five times daily. Chi-square test and multinomial logistic regression were applied to determine statistical differences between the variables using PASW v. 18.0 software (SPSS Inc., Chicago, IL). Results: The male-female ratio was 2:1 with an average children age of 8.9 ± 3.65 years and 16.1 ± 1.23 years in adolescents. The risk for adenoids was seen in 49.4 % of children (OR; 2.6: 95% CI: 1.63-4.06) while allergic fungal sinusitis (18.1%, OR: 2.7; 95% CI: 1.12-6.57) and nasal polyps (26.3%, OR: 2.3; 95% CI: 1.07-4.86) was commonly seen in adolescents. Bacterial culture rate was positive in 46.8% of the total subjects of which Staphylococcus aureus was the most common bacteria (59.1%) followed by Streptococcus pnuemoniae (21.2%), Klebsiella sps (11.4%), Pseudomonas aeruginosa (11.4%) and \(β\) hemolytic streptococci (1.1%). Streptococcus pneumonia (63.2%) was commonly identified in younger children and Pseudomonas aeruginosa (80%) was mostly seen in adolescents. High antibiotic resistance in Staphylococcus aureus was seen towards gentamicin (73%) and co-trimoxazole (64%), Streptococcus pnuemoniae to gentamicin (58%), co-trimoxazole (68%) and meropenem (32%), Pseudomonas aeruginosa to co-trimoxazole (100%), cefatoximine (60%) and cefatazidime (50%) while Klebsiella sps to gentamicin (80%) and co-trimoxazole (60%). Streptococcus aureus showed high sensitivity to cefatoximine (95.8%) and Streptococcus pnuemoniae for ofloxacin (100%), ciprofloxacin (89.5%) and cefazolin (89.5%). Pseudomonas aeruginosa showed a high sensitivity for amikacin (100%) and ciprofloxacin (80%) and Klebsiella sps for amikacin (100%). Prompt detection and treatment of bacterial infections may reduce the severity of CRS episodes and enhance patient outcomes. It is also critical to think about how these discoveries may affect treatment plans and public health campaigns in South India. Conclusion: Significant regional-specific variation and high antimicrobial resistance in the cultures of CRS patients warrant an urgent need for early initiation of personalized interventions for better management of infectious disease. The elevated rates of antibiotic resistance observed in all microbial isolates, including Staphylococcus aureus, Streptococcus pneumoniae, Pseudomonas aeruginosa, and Klebsiella sps underscore the imperative for the prompt initiation of personalized interventions and management strategies in the pediatric and adolescent population suffering from CRS.